Cyclic-di-GMP signalling in 3-chloroaniline biodegradation by comamonas testosteroni - Phang, William Jak Soon (2014)
Biofilm mode of growth offers multiple benefits in the biodegradation of toxic xenobiotics. This project aims to enhance the biofilm formation capability of Comamonas testosteroni WDL7 through expressing a protein YedQ that synthesizes c-di-GMP, a key signaling molecule in biofilm formation. A C. testosteroni mutant containing pYedQ2 plasmid was constructed and the effects of c-di-GMP overproduction on phenotype, biofilm formation, and 3-chloroaniline degradation were investigated. The mutant exhibited smaller cell colony and enhanced exopolysaccharide production and inhibited swimming motility. A significant increase in biofilm formation was observed in comparison with wild type. The growth and biodegradation profile of C. testosteroni WDL7 (pYedQ2) under low surface/volume ratio (culture flasks) could be described by the Monod model. In high surface to volume ratio situation, the mutant showed less planktonic growth but a significantly higher contribution of biofilms in 3-chloroaniline degradation. Future experiments will focus on better quantification of biofilm biomass, verification of degradation efficiency and gene expression due to elevated c-di-GMP level.